PERAN KEPALA SEKOLAH DALAM MENINGKATKAN KETERAMPILAN GURU MEMBUAT RENCANA PEMBELAJARAN DI SDN TEMBULUN 2 - Yudha, Vidia Pandji; Aceng Hasani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to analyze the role of school principals in improving teachers' skills in preparing Learning Plans (LP) at SDN Tembulun 2. This study uses a qualitative approach with a case study method. Data collection techniques are carried out through in-depth interviews, observations, and documentation. The results of the study show that school principals have a strategic role in providing supervision, guidance, and training to teachers, which has a positive impact on improving their skills in developing Learning Plans. Obstacles faced by teachers in the preparation of Learning Plans, such as time constraints and lack of formal training, can be overcome through collaborative strategies and the use of technology facilitated by school principals. Improving teachers' skills in designing Learning Plans has been proven to be able to increase the effectiveness of the learning process, so that the quality of education at SDN Tembulun 2 has improved. This research emphasizes the importance of the role of school principals in developing teacher competencies and improving the quality of learning in elementary schools.